K-MEANS CLUSTERING METHOD FEASIBILITY OF SCHOOL BUILDING REHABILITATION IN KABUPATEN ASAHAN - Nurhani, Irma; Manurung, Nuriadi; Rahayu, Elly (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Royal Kisaran, 2025)
Abstract: School building construction is an important part of educational facilities and infrastructure. Many elementary school buildings in Asahan Regency are damaged, unfit for use or lack facilities including classrooms and other supporting infrastructure. The results of the selection that are not transparent in deciding the feasibility of rehabilitation and construction of elementary school buildings are often subjective and time-consuming. This causes decisions to be taken that cannot be made as quickly as possible and inequality, where schools that actually need rehabilitation more do not get priority for rehabilitation. The purpose of this study is to implement data mining in the selection of school building construction projects with the K-Means clustering algorithm in clustering the feasibility of rehabilitation of elementary school building construction. The results of this study found 31 elementary schools that are eligible for school building construction rehabilitation and 4 are not eligible for school building construction rehabilitation. This study is expected to provide a significant contribution in increasing the efficiency of school building construction selection and more transparency towards elementary school buildings to be rehabilitated. Keywords: education authorities; k-means; rehabilitation and construction of school buildings. Abstrak: Pembangunan gedung sekolah ialah bagian penting dalam sarana dan prasarana pendidikan. Banyak gedung Sekolah Dasar di Kabupaten Asahan menderita kerusakan, tidak layak pakai atau kekurangan fasilitas meliputi ruang kelas dan infrastruktur pendukung lainnya. Hasil penyeleksian yang bersifat tidak transparan dalam memutuskan kelayakan rehabilitasi dan pembangunan gedung Sekolah Dasar sering kali bersifat subjektif dan memakan waktu lama.Hal tersebut menyebabkan keputusan yang diambil tidak dapat dilakukan secepat mungkin serta ketimpangan, dimana sekolah yang sebenarnya lebih membutuhkan rehabilitasi justru tidak mendapatkan prioritas untuk direhabilitasi. Tujuan penelitian ini ialah mengimplementasi data mining pada pemilihan proyek pembangunan gedung sekolah dengan algoritma K-Means clustering dalam mengcluster kelayakan rehabilitasi pembangunan gedung sekolah dasar. Hasil Penelitian ini terdapat 31 sekolah dasar layak untuk direhabilitasi pembangunan gedung sekolah dan 4 tidak layak untuk direhabalitasi pembangunan gedung sekolah. Penelitian ini diharapkan dapat memberikan kontribusi signifikan dalam menaikkan efisiensi penyeleksian pembangunan gedung sekolah dan lebih transparansi terhadap gedung sekolah dasar yang akan direhabilitasi.Kata kunci: dinas pendidikan; k-means; rehabilitasi dan pembangunan gedung sekolah.